Bioethical dilemmas in geriatrics: madical decision-making - Mercado R., Cristián (Acta Bioethica, 2001)
Chile is a country that is growing older. Sanitary resource allocation is insufficient and there exists inadequate training in Geriatrics and Bioethics. Aging determines greater susceptibility and vulnerability when facing pathological aggressions. The elderly present a high prevalence of chronic diseases which translates into a greater demand for health assistance. Bioethical principles are frequently addressed in geriatric practice and give rise to complex discussions. Thus, knowledge and full command of those principles are fundamental. Discussion is the basic tool for decision-making and must be realized by the interdisciplinary team, together with the patient's family or proxy. If we consider we do not treat diseases but sick people, we will find in the elderly a very particular type of patient; one with particular psychosocial conflicts. Taking into account patient's values and ethical principles as well is a must. This paper attempts to analyze, from the bioethical standpoint, the dilemmas posed by decision-making in Geriatrics.